Physiological, transcriptomic, and genomic analysis unravels the response of Tatary buckwheat root to high ammonium stress - Liu, Changying; Wang, Jiting; Qiu, Qingcheng; Xu, Daiying; Wu, Xi; Yin, Junjie; Zheng, Xiaoqin; Tan, Maoling; Wan, Yan; Sun, Wenjun; Xiang, Dabing (Frontiers in Plant Science, 2025)
Toxicity caused by high ammonium severely affects plant growth and crop production, it is urgent to breed high NH4+-tolerant and high-yield plants. However, the molecular mechanisms on the response and tolerance of plant to high NH4+ remain poorly understood. In this study, four different genotypes of Tartary buckwheat (Fagopyrum tataricum Garetn.) were used to investigate the molecular mechanism on high NH4+ response by integrating physiological, transcriptome, and genome analysis. The root and shoot growth of Tartary buckwheat (TB) seedlings were significantly inhibited by 50 and 100 mmol/L NH4+ treatments. High NH4+ inhibits root growth by affecting activities of antioxidant enzymes, thereby suppressing plant growth. In total 426 high NH4+-responsive common differentially expressed genes (DEGs) were identified in TB. Most of DEGs involved in antioxidant enzyme system, hormone signaling, and N transport and assimilation were down-regulated by high NH4+. Co-expression analysis suggested the possible hub genes in regulating high NH4+ response, such as FtNRT1.14, FtMYB61/52, FtbZIP6/34, FtNAC72/73, and FtLTP14. 19 small secreted peptides (SSPs) encoding genes were respond to high NH4+, including FtCLE7 and FtCEP3. The up-regulation of FtCLE7 expression and down-regulation of FtCEP3 expression may help plants to optimize root perception and response to high NH4+. Additionally, 443 genotype-specific high NH4+-responsive DEGs with sequence variation were identified by integrating transcriptome and genome re-sequencing data. The TFs such as MYB, MADS, and LBD genes and the RLKs such as FtBAM1/3 may help TB to adapt to high NH4+. This work provides useful information for investigating the mechanisms on TB respond to high NH4+, and the candidate genes for breeding TB with high NH4+ tolerance were suggested.